Clinical outcomes of closed, displaced phalangeal neck fractures in children with different types of kirschner wire fixation: A retrospective observational study - Wu, Chunxing; Song, Jun; Ning, Bo; Mo, Yueqiang; Wang, Dahui (Frontiers in Pediatrics, 2023)
Objectives: Inappropriate treatment of Closed displaced phalangeal neck fractures (CDPNF) in children usually leads to poor outcomes.This study was to evaluate the clinical outcomes of closed/open reduction, age, and different types of fracture and Kirschner wire (K-wire) fixation in the treatment of CDPNF. Materials and methods: Participants: Sixty patients (male, 46 and female,14; right-handed,35 and left-handed, 25; mean age, 7.9-years-old [range, 1.0–14.5 years]) who had CDPNF were included. Preoperative X-rays showed that the fractures were displaced and exhibited obvious deformities. Interventions ：First, reduction (four cases of open reduction and 56 cases of closed reduction) was performed followed by percutaneous K-wire fixation (cross fixation, 24 cases; longitudinal and slanting fixation, 17 cases; homolateral fixation, four cases; and single longitudinal fixation, 15 cases, ) and immobilized by cast. X-ray examination following removal of the K-wires showed that the fractures were healed; the criteria for fracture healing were callus formation and the absence of fracture lines. Clinical outcome and radiographs between groups were compared. Results: According to the visual analogue scale, the pain scores were excellent. According to the Al-Qattan Grade system(AGS),all the patients presented with closed, type II phalangeal neck fractures,the results were excellent in 36 cases (36/60, 60%), good in 15 cases (15/60, 25%), fair in 5 cases (5/60, 8.3%) and poor in 4 cases (4/60, 6.7%) . There were significant differences in different fracture type groups (P=0.013*), operation age groups (P=0.025*) and open/closed reduction groups (P=0.042*). There was no significant difference in K-wire fixation type groups (P>0.05) Conclusions: Patients with open reduction, the more serious fracture type, the older at the operation, were more likely to have poor AGS result. Different K-wire fixation types for CDPNF in children had the same satisfactory results.